2023
DOI: 10.4103/1673-5374.353482
|View full text |Cite
|
Sign up to set email alerts
|

In vivo astrocyte-to-neuron reprogramming for central nervous system regeneration: a narrative review

Abstract: The inability of damaged neurons to regenerate within the mature central nervous system (CNS) is a significant neuroscientific challenge. Astrocytes are an essential component of the CNS and participate in many physiological processes including blood-brain barrier formation, axon growth regulation, neuronal support, and higher cognitive functions such as memory. Recent reprogramming studies have confirmed that astrocytes in the mature CNS can be transformed into functional neurons. Building on in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Many authors are exploring the potential of astrocytes to generate new neurons, however they are focused on artificial reprogramming or transdifferentiation (Talifu et al, 2022). This is the first description of this phenomenon observed in vivo in wild type animals .…”
Section: Resultsmentioning
confidence: 99%
“…Many authors are exploring the potential of astrocytes to generate new neurons, however they are focused on artificial reprogramming or transdifferentiation (Talifu et al, 2022). This is the first description of this phenomenon observed in vivo in wild type animals .…”
Section: Resultsmentioning
confidence: 99%
“…They upregulate multiple genes, augment cytoskeletal dimensions, extend their processes, increase glial fibrillary acidic protein expression, and enhance immunoreactivity, ultimately forming glial scars. [ 19 , 20 ] In addition, activated astrocytes release Glu, and when excess Glu binds to the extrasynaptic NMDAR (N-methyl-d-aspartate receptor), brain-derived neurotrophic factor (BDNF) synthesis is reduced, affecting neuronal integrity. [ 6 , 21 ] Stimulation of astrocytes surrounding the BBB by metabolic glutamate receptor-1 results in elevated Ca2 + levels.…”
Section: Depression and Central Nervous Inflammationmentioning
confidence: 99%
“…Since the discovery that ectopic transcription factor (TF) expression can drive cell fate [ 10 ], attention has been focused on developing interventions to replace lost cells in models of injury or disease. Many publications have since identified effective methods to convert somatic cells to other cell types [ 11 , 12 ], including neuronal cells, both in vitro and in vivo [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In the context of the central nervous system (CNS), a number of groups have examined the ectopic expression of TFs in the CNS and demonstrated that proneural TFs such as Ngn2 [ 23 ] and Ascl1 [ 20 , 24 ] and the neuronal differentiation TF Neurod1 [ 25 , 26 ] can convert glial cells to neurons [ 27 ].…”
Section: Introductionmentioning
confidence: 99%